Frequency and factors associated with psycho-emotional disorders in medical students of National University of Lambayeque, Perú - Puescas-Sánchez, Pablo Ronald (2020)
Objetive: To identify the frequency and factors associated with psycho-emotional disorders in medical students of the Lambayeque region. Material and Methods: We conducted a cross-sectional study, analytic in a sample of 172 students, distributed by stratified random sampling according to university study, who were administered the SCL-90 to determine psychopathological symptoms. Statistical analysis: Data obtained were analyzed by SPSS 17.0 program, using descriptive statistics with absolute frequencies, mean, SD; inferential statistics with chi2 tests for the bivariate analysis and generalized linear models for multivariate analysis. Results: 72.7% was comprised of males, the predominant marital status was single with 87.2%, 11.0% currently working and had family and personal history of psycho-emotional disorders 1.7% and 2 3% of students tested disorders occur most often: obsessions and compulsions 99.4%, 98.5% somatization, obsessive disorders appear to be associated with years of education (PR = 0.97, CI (95% ) = 0.95 - 0.98), with having children (PR = 0.49), CI (95%) = O.24-0.75) and with having a job (PR = 3.10, CI (95%) = 2.74 to 3.58). Conclusion: We found a high incidence of psycho-emotional disorders in medical students of the Pedro Ruiz Gallo National University.